Clustered Regularly Interspersed Short Palindromic Repeats Gene Editing: Precision Medicine and Newer Therapies for Retinal Dystrophies - Mayank Bansal (Delhi Journal of Ophthalmology)
Personalized medicine with the development of targeted therapies toward clinical disorders is predicted to be the future of medicine. Ophthalmology is at the forefront of the development of newer therapies, as the eye forms an excellent target for the development of such therapies given the accessibility of eye to interventions, the immune privilege, and ability to directly monitor response to interventions. Within ophthalmology, inherited retinal dystrophies (IRDs) form a dynamic area of research, as no definitive therapy exists for such a blinding eye condition. There are various approaches in research, and in early clinical trials for treating IRDs including Food and Drug Administration approved gene therapy Voretegene neparvovec for retinal pigment epithelium 65 gene associated Leber’s Congenital Amaurosis, Argus II bionic eye, and regenerative therapies such as stem cells. This narrative review delves deeper into Clustered Regularly Interspersed Short Palindromic Repeats gene editing-based therapies for the management of IRDs, the advantages, limitations, current research, and future direction.